Review on vortex simulation using computational fluid dynamic (CFD) - Nurhikmah F.; Zahari N.M.; Zawawi M.H.; Aziz N.A.; Azman A. (American Institute of Physics Inc., 2023)
In the present work, a numerical study was carry out to study the existence of strong vortices in the flow behavior of dam reservoir. The occurence of vortex breakdown is extremely complex and quite difficult to acquire enough details experimentally. To fully understand and comprehend the mechanisms that involved, numerical study is required. With the evolution of computer devices and numerical techniques, a computational approach seemed very appealing to get the additional information regarding the structure of the breakdown. Besides, the identifying of the various parameters affecting its occurrence and development can be obtained to. Getting supplementary insight into the physics itself of the circumstance has been another ambition. This paper reviews recent published works on CFD (computational fluid dynamic) simulations of vortex in hydraulic intake. 2020 Author(s).